Leadership in Action : Issues and Observations - The Seven Deadly Sins of Leadership - Torres, Cresencio (Center for Creative Leadership, 2003)
The challenge that leaders must accept and meet to break the spiraling cycle of disillusionment with leaders in every aspect of our lives-business, government, religion, and education- is to identify this malfeasance and determine what can be done about it.